Toxicity Studies on Leaf Extracts of Alternanthera brasiliana (L.) Kuntze and Alternanthera bettzickiana (Regel) Voss - Kasthuri O R, Ramesh B (Journal of Applied Pharmaceutical Science, 2018)
Herbal medicine is the source for the search of many novel therapeutic compounds in developing countries. Before used as medicine, drugs from plant origin must be ensured as safe. Objective: The present work focused to study the in vivo and in vitro toxicity effects of hydroethanolic leaf extracts of Alternanthera brasiliana (A. brasiliana) and Alternanthera bettzickiana (A. bettzickiana). Methods: Sub-acute toxicity studies of hydroethanolic leaf extracts of A. brasiliana and A. bettzickiana were carried out in vivo on mice. 11 groups of albino mice were treated with five different doses of the hydroethanolic leaf extracts of A. brasiliana and A. bettzickiana orally for 14 days. General appearance and behavior were observed for 14 consecutive days. Effect on hematological parameters and histopathological changes were also monitored. Cytotoxicity was assessed by observing its toxicity in vitro against DLA cell line by using MTT assay. Results: Sub-acute toxicity studies results showed that up to the tested dose of 2000 mg/kg bwt in both extract treatments, throughout the 14 days of treatment, the extract does not produced any toxicity symptoms. MTT assay indicated that both leaf extracts exhibited significant concentration-dependent in vitro cytotoxic activity against DLA cell line. Hydroethanolic leaf extract of A. bettzickiana exhibited more potent cytotoxic effects on DLA cells than A. brasiliana extract. Conclusion: No toxicity related symptoms were observed in different doses of leaf extract treated mice groups. So the LD50 values of the tested leaf extracts were more than 2000 mg/kg bwt.
Keywords: Cytotoxicity, LD50, hematology, MTT assay, histopathology.